Substitute for polyethylene (PE) films: A novel attapulgite super absorbent polymer applied in a semi-humid drought-prone region of the Loess Plateau - Xiaofan Pan; Hengjia Zhang; Shouchao Yu; Haoliang Deng; Xietian Chen; Chenli Zhou; Fuqiang Li; Haiyan Li (Agricultural Water Management)
Residual film and microplastics are widely used to prevent soil water loss in arid farming areas of the Loess Plateau, China; however, pollution and farm land quality decline plaque this management strategy. To address this, a field experiment was conducted at the dry farming demonstration site in Huating City, Gansu Province to test a novel amendment of attapulgite super absorbent polymer (A-SAP). We tested different A-SAP dosages: 30 (KL), 45 (KM), and 60 kg ha−1 (KH); different coverage methods: transparent plastic film half mulching (WH), transparent plastic film full mulching (WW), black plastic film half mulching (BH), black plastic film full mulching (BW), and straw mulching (SM), with no film and no application of A-SAP as a control (CK). We built a comprehensive growth evaluation system for spring maize, select the best soil moisture conservation strategy, and provide a theoretical basis for sustainable maize production in the semi-arid area of the Loess Plateau. The results showed that all moisture conserving treatments improved soil quality compared with CK, the application of A-SAP was more conducive to rainwater infiltration during precipitation events, increased the number of soil microorganisms and soil enzyme activity, however, there was no effect of increasing soil temperature. Soil moisture retention strategies increased spring maize plant height, stem diameter, leaf area index, and dry matter accumulation, and regulated yield components, promoting spring maize yield formation, improve water productivity and economic benefits. Taking into account indicators such as soil hydrothermal, soil microbial quantity, soil enzyme activity, spring maize growth, yield, water productivity and economic benefit, the application of 45 kg ha−1 attapulgite super absorbent polymer had the best overall effect. Therefore, the application of 45 kg ha−1 of A-SAP can reduce pollution from residual films and microplastics and realize environmental protection while guaranteeing stable yields of spring maize in the semi-humid drought-prone region of the China’s Loess Plateau.